The Event Communication Vector of Efficiency of Moroccan Large Companies - Najwa El Omari; Toufik Majdi (Universitas Pelita Harapan, 2016)
The event communication has for objective to give another dimension to the company or to the brand, by bringing it out of its daily life and by developing relations with its target public, around their centers of interests. It may be by sharing the same passions, by making live feelings to a group, by federating and by creating links; because today we need a more emotional and more real component.Since a few years, the event communication seems to be